IMPLEMENTATION SOCIAL PERSONAL GUIDANCE PROGRAM IN DEVELOPING STUDENT'S EMOTIONAL INTELLIGENCE AT ISLAMIC SENIOR HIGHT SCHOOL (MAL) UIN SU MEDAN - Abdurrahman Abdurrahman; Yafizham Yafizham; Andi Suhendra Siregar (Universitas Dharmawangsa Medan, 2020)
The purpose of this research is to find out the implementation of the Social Personal Guidance Program in Developing Students' Emotional Intelligence at Islamic Senior High School (MAL) UIN SU Medan. This study used a qualitative field method with data collection techniques using interviews, observation, and documentation. The results showed that: 1) The Concept of Social Personal Guidance in Developing Student Emotional Intelligence at Islamic Senior High School(MAL) UIN North Sumatra is a counseling teacher giving direction to students related to personality problems or social and social morals, by using independent and group methods, 2) Implementation of Social Personal Guidance in Developing Student's Emotional Intelligence at Islamic Senior High School (MAL) UIN North Sumatra is carried out on a scheduled basis and carried out by two methods, namely independently and in groups. Also, the social personal guidance process is assisted by the homeroom teacher and parents of each student, 3) Barriers to Implementing Social Personal Guidance in Developing Student Emotional Intelligence at Islamic Senior High School (MAL) UIN North Sumatra are a) lack of awareness of students in following and practice the guidance that has been given, b) lack of parental attention, c) the limited number of BK teachers, and d) limited facilities. 4) Efforts Made in Overcoming Barriers to Social Personal Guidance in Developing Student's Emotional Intelligence at Islamic Senior High School (MAL) UIN North Sumatra are a) making students aware of the seriousness of students in following the guidance process, b) increasing the number of BK teachers, c) involving the participation of teachers others, especially homeroom teachers, d) maximize the role of the principal in overseeing the counseling process